Dilemma of natural resource abundance: a case study of Kuwait - Aljarallah, Ruba A.; Angus, Andrew (SAGE, 2020)
There is a lively debate about the relationship between a nation’s natural resource abundance and economic growth. Some view natural resource abundance as a curse, whereas others view it as a blessing. This study examines the economic, social, and political effects of resource abundance in an oil-rich country, Kuwait, using data from 1984 to 2014. This study analyzes the short- and long-run impacts of resource rents on per capita gross domestic product (GDP), productivity, human capital, and institutional quality. The study reveals through autoregressive distributed lag modeling and error correction modeling that resource rents increase per capita GDP merely in the short-run; however, resource rents deteriorate productivity, human capital, and institutional quality in both the short and the long-run. These results indicate that, for Kuwait, the overreliance on its natural resources has been detrimental over the long-run. The study suggests that there is a need to improve the quality of institutions and enhance the level of human capital to get economic sustainability and development over time.
Keywords: agricultural and natural resource economics; economic science; social sciences; human resource development; human resources management; management; political institutions; political science; economic development; political economy